Os heróis da literatura - Perrone-Moisés, Leyla (Estudos Avançados, 2011)
In the last decades the hypothesis of "the end of literature" has been put forward. It actually concerns the end of one kind of literature, that of high modernity. At the same time, many novels were published whose main character is a famous writer from the end of the 19th century or the first half of 20th: Rimbaud, Flaubert, Dostoievsky, Henry James, Virginia Woolf, Pessoa and others. The aim of this article is to examine the causes and the features of these particular novels. Do "post-modern" writers look at their predecessors as heroes and models? Are they mourning a brighter phase of literature and comparing it with the current one? What is the relation between this kind of fiction and the old biographies? What are the formal contributions of this new sub-gender?